PENERAPAN MEDIA PEMBELAJARAN POWERPOINT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI KELAS XI SMA AL-KHAIRAAT WAYAUA KECAMATAN BACAN TIMUR SELATAN - Sarkandi, Alfajri; Alnursa, Darling Surya (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
The purpose of this study is to determine the application of PowerPoint media to student learning outcomes in geography in grade XI of Al-Khairaat Wayaua Senior High School, Bacan Timur Selatan District. Classroom Action Research (CAR) was used. Classroom action research is a form of reflective research that involves taking specific actions to improve and/or enhance classroom learning practices professionally. Based on the results of the study, the application of PowerPoint media in grade XI of Al-Khairaat Wayaua Senior High School, Bacan Timur Selatan District, in cycle I, the average student score was only 62.08, with a learning completion rate of 37%. Meanwhile, 63% of students failed to meet the Minimum Completion Criteria (KKM). This condition indicates that learning outcomes in cycle I were still unsatisfactory. However, in cycle II, there was a significant improvement. The average student score increased to 78.33, with a learning completion rate of 92%. This indicates that most students have achieved the specified KKM.